Capital Mobility in India : Does Sterilization Matter? - Gupta, Kirti; Ahmed, Shahid (Indian Journal of Finance, 2019)
This paper examined a linkage between capital flows, floating but managed exchange rate, and conduct of monetary policy in India. The sporadic surge in capital inflows have caused a great deal of fluctuations on the domestic exchange rate. Considering this, we analyzed different channels through which the RBI intervened in the foreign exchange market to provide greater leeway in conduct of the monetary policy. The study found that after the global financial crisis, RBI has proactively been engaged into selling of foreign currency concurrently with buying of dollars in the forex market so that the Indian rupee can be stabilized, and currency volatility can be diminished. However, prior to the crisis in the aftermath of unprecedented capital inflows, foreign reserves were accumulated to stabilize the exchange rate. We investigated the extent of sterilization of capital inflows by deploying a sample of quarterly data over the period from 2002 - 2015 and found that reserve money was sterilized to a significantly higher degree during the pre-crisis period (2002-2007) than the post-crisis period (2008-2015). The impact of direct intervention by the central bank was found largely effective in the post-crisis period. Further, this study highlighted various challenges emanating from sterilization to the economy in terms of burden of interest payment on the government securities and less availability of funds as needed for developmental expenditures. Full sterilization of reserve money may reduce exchange rate volatility and can provide much control over domestic monetary conditions; however, the risks of financial instability remain present.